Professional responsibility - Moliterno, James E., 1953- (2020)
"Provides coverage of materials typically taught in law school about the law and ethics that govern relationships lawyers have with clients, other lawyers, the profession, the justice system, and the public. Audience: Law students"--
Introduction and the role of lawyer -- Regulation of the legal profession -- Controls on lawyer conduct -- Formal aspects of the lawyer-client relationship -- Confidentiality -- Conflicts of interest -- Duties to third parties -- Duties to the legal system and society -- Special role-related duties -- Advertising and solicitation -- Judicial conduct.
Includes index.
Keywords: Legal ethics -- United States; Lawyers -- Malpractice -- United States; Lawyers -- Malpractice; Legal ethics; United States; Study guides; Study guides